1987
DOI: 10.1520/cca10400j
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Slump Cone and V-B Tests as Measures of Workability for Fiber-Reinforced and Plain Concrete

Abstract: In this paper, two popular measures of workability, namely, slump and V-B time, are compared for plain and steel (hooked) fiber-reinforced concrete. The results are based on experiments made on both types of concrete with and without high-range, water-reducing admixture. The fibers were 50 mm (2 in.) long with deformed ends glued together side by side into bundles (collated) with a water-soluble glue. The W-C ratio varied from 0.3 to 0.62. The air content ranged from 2 to 12%. In terms of workability, the whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The workability of different concrete blends was determined following ASTM C143. 75 To evaluate the mechanical performance of concrete, samples were prepared and cast that had a length of 12 inches and a diameter of 6 inches, as shown in Figure 4a. The concrete was filled in three layers, and every layer was compacted 25 times using a steel rod.…”
Section: Sample Preparation and Testingmentioning
confidence: 99%
“…The workability of different concrete blends was determined following ASTM C143. 75 To evaluate the mechanical performance of concrete, samples were prepared and cast that had a length of 12 inches and a diameter of 6 inches, as shown in Figure 4a. The concrete was filled in three layers, and every layer was compacted 25 times using a steel rod.…”
Section: Sample Preparation and Testingmentioning
confidence: 99%
“…38 Due to the relatively large surface area of fibers, water use has increased. [39][40][41][42][43] Concrete requires more energy to flow by its weight because the aggregate and fibers in the blends have higher friction with one another. 44 The results showed that the slump value declined as the quantity of waste rope fiber in the blend raised.…”
Section: Engineering Propertiesmentioning
confidence: 99%